Chemist on sabbatical: Anything to do with a botanical garden? / Dr. Nurhuda Manshoor and Dr. Gurmeet Kaur Surindar Singh - Manshoor, Nurhuda; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
For nine months, from April to December 2023, I am on sabbatical leave at the Royal Botanic Garden, Kew, London. The purpose of this sabbatical is for me to document plant species with significant phytochemicals and work on research related to plant-based commercial health products. The selection of a botanic garden over conventional research laboratories and universities for my research endeavours stems from the intrinsic alignment of my work with the realm of plants and their pivotal role in scientific exploration. Moreover, the discerning choice is further substantiated by the fact that the Royal Botanic Gardens, Kew, boasts the distinction of housing the world's most extensive and diverse botanical and mycological collections. Its living collections consist of some of the 27,000 taxa, while the herbarium has over 8.5 million preserved plant and fungal specimens. Kew Gardens holds further collections of scientific importance, including a Fungarium, which houses approximately 1.25 million specimens of dried fungi, a plant DNA bank, and a seed bank. The Library, Art, and Archives are one of the world's largest botanical collections, with more than 750,000 volumes, including books, botanical illustrations, photographs, letters and manuscripts, periodicals, and maps. The illustration collection alone contains more than 175,000 prints and drawings of plants.